(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The positive and negative impacts of technology and modern developments in the field of lexicography and dictionary making are shown in this research. The research contrasts the three types of dictionaries in an objective way written, electronic and online. Some different users were interviewed by the researchers to ask them about the advantages and disadvantages of these dictionaries. This study confirms that the method of compiling dictionaries is positively and negatively influenced by inventions and new technologies. It also finds that each of the three types of dictionaries has its own merits and demerits. In order to expand our dictionaries, the study suggests gaining positively from the machine and internet revolution. It concludes that the ideal dictionary is the one that meets the needs and demands of the consumer. The research finds that for every user, the dictionary remains an indispensable tool.